2019
DOI: 10.3928/02793695-20190821-02
|View full text |Cite
|
Sign up to set email alerts
|

Caring for People With Young Onset Dementia: An Interpretative Phenomenological Analysis of Family Caregivers' Experiences

Abstract: People with young onset dementia (YOD) experience many unique challenges. Similarly, family caregivers experience changing personal, familial, and societal roles. However, YOD is under recognized and under resourced with a lack of dedicated models of care. The current study explored family members' experience of caregiving for persons with YOD to identify barriers and opportunities to accessing support. Qualitative interviews were conducted with six family caregivers, using interpretative phenomenological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Similar to prior research, in our study insufficient role fulfilment of the person having the behavioral variant of frontotemporal dementia led to pre-diagnostic role ambiguity in family members (Kilty et al, 2019). We found that early symptoms affected the role, level of involvement, and the position of the person having frontotemporal dementia within the family system.…”
Section: Interpretation Of Findingssupporting
confidence: 87%
“…Similar to prior research, in our study insufficient role fulfilment of the person having the behavioral variant of frontotemporal dementia led to pre-diagnostic role ambiguity in family members (Kilty et al, 2019). We found that early symptoms affected the role, level of involvement, and the position of the person having frontotemporal dementia within the family system.…”
Section: Interpretation Of Findingssupporting
confidence: 87%
“…Regarding unique themes, persons with young onset dementia desired practical strategies for managing their symptoms that were appropriate for their current level of functioning (Ducharme et al, 2013;Hewitt et al, 2013;Holthe et al, 2018;Johannessen & Moller, 2013;Rabanal et al, 2018) and to learn to cultivate new skills and engage in hobbies to promote their health and wellbeing (Cations et al, 2017;Hewitt et al, 2013;Holthe et al, 2018;Kimura et al, 2015;Robertson & Evans, 2015). Caregivers hoped to learn strategies to better manage persons' with young onset dementia behavioral symptoms (Kilty et al, 2019;Kimura et al, 2015;Larochette et al, 2019;Millenaar et al, 2014;Wawrziczny et al, 2017b), navigate practical tasks (e.g., arranging care, navigating medical appointments, financial support, and advanced care options), and provide support without needing to excessively "monitor" persons with young onset dementia (García-Toro et al, 2020;Mayrhofer et al, 2020;Van Rickstal et al, 2019;Wawrziczny et al, 2017b). Caregivers also sought to learn to prioritize their own mental health and emotional or practical needs (Dourado et al, 2018;Johannessen et al, 2017;Larochette et al, 2019;Svanberg et al, 2010).…”
Section: Domain 3: Desired Content For Supportive Servicesmentioning
confidence: 99%
“…Systematic reviews indicate high rates of clinically elevated emotional distress (e.g., depression and anxiety) (Spreadbury & Kipps, 2019a) for both persons with young onset dementia and caregivers, which can negatively impact their shared communication, relationship quality, and illness management (Kilty et al, 2019;Millenaar et al 2016). These rates are not surprising given the difficult emotions (e.g., sadness, anger, and grief) and substantial stressors (e.g., loss of employment, increased caregiving, and change in roles) that accompany young onset dementias (Bannon et al, 2020;Spreadbury & Kipps, 2019a, 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…Both persons with young-onset dementia and their partners are markedly impacted by the diagnosis. They both endorse high rates of chronic emotional distress (e.g., depression and anxiety), which can negatively impact relationship quality and communication over time (Kilty et al, 2019; Millenaar et al, 2016). These rates are not surprising, given the number of stressors (e.g., loss of employment, increased caregiving, and change in roles) and difficult emotions (e.g., sadness, anger, and grief) that couples can experience together after symptom onset (Bannon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%